Natural Methods for Preventing Fish Spoilage Using Indian Terminalia spp. Extracts: Growth Inhibition of Shewanella spp. - Webster, Samantha Jayde; Wright, Mitchell Henry; Greene, Anthony Carlson; Cock, Ian Edwin (Pharmacognosy Communications)
Introduction: Shewanella spp. are a major cause of fish spoilage. Termina- lia spp. have a long history of medicinal uses, including being used to treat bacterial infections. Despite their well-established antibacterial properties, the Indian Terminalia spp. have not been tested for the ability to inhibit the growth of fish spoilage bacteria. Methods: Solvent extracts were prepared using Indian Terminalia spp. known to inhibit microbial growth. The growth inhibitory activity of the extracts was investigated by disc diffusion assay against four Shewanella spp. environmental isolates. Their MIC values were calculated to quantify and compare their relative efficacies. Toxicity was determined using the Artemia franciscana nauplii bioassay. Results: Extracts prepared from several Indian Terminalia spp. displayed potent anti- bacterial activity in the disc diffusion assay against the environmental She- wanella spp. isolates. The methanolic T. chebula fruit extract was particu- larly effective at inhibiting Shewanella spp. growth, with MIC values of 198, 329, 162 and 176 µg/mL against S. putrefaciens, S. baltica, S. frigidimarina and S. loihica respectively. The T. chebula fruit ethyl acetate and T. catappa fruit methanolic extracts were similarly potent, with MIC values generally substantially <1000 µg/mL against all Shewanella spp. In contrast, the T. catappa bark and all T. arjuna extracts were only moderate growth inhibitors (MIC values 1000-5000 µg/mL). All other extracts were either inactive or of only low growth inhibitory activity. All the extracts were nontoxic, with all recorded LC50 values substantially >1000 µg/mL. Conclusions: The potent growth inhibitory activity of the methanolic and ethyl acetate T. chebula fruit extracts against all Shewanella spp. indicates their potential in the pre- vention of fish spoilage. Furthermore, the lack of toxicity of these extracts indicates their suitability for use as natural fish preservatives.
Keywords: Food Spoilage; Microbial Rancidity; Shewanella; Terminalia chebula; Terminalia catappa; Terminalia arjuna; Natural Preservative.